Comparative genomics of bdelloid rotifers: Insights from desiccating and nondesiccating species - Nowell, Reuben W.; Almeida, Pedro; Wilson, Christopher G.; Smith, Thomas P.; Fontaneto, Diego; Crisp, Alastair; Micklem, Gos; Tunnacliffe, Alan; Boschetti, Chiara; Barraclough, Timothy G. (PLOS Biology, 2018)
Author summary Bdelloid rotifers are microscopic animals that live in freshwater habitats throughout the world. Two life history characteristics distinguish these common invertebrates as extraordinary. First, they have existed for millions of years apparently without sex: males have not been reported, and females produce genetically identical daughters via parthenogenesis. Second, most bdelloid species are highly resilient to desiccation and can survive without water for extended periods of time (a process known as anhydrobiosis). These 2 attributes have been predicted to leave signatures in bdelloid genomes. Here, we present new draft genomes for 3 bdelloid species and employ comparative genomics to explore the potential impacts of bdelloids’ unusual lifestyle on genome structure and content. We find that many proposed genomic consequences of asexuality and desiccation tolerance do not hold true for all species. The genomes of bdelloids may be more similar to those of other animals than previously thought, though a remarkable exception is the high proportion of genes acquired horizontally from nonmetazoan taxa. Our findings necessitate a reevaluation of the effects of asexuality and desiccation on genome evolution in bdelloid rotifers.